Combined and independent impact of coronary artery calcification and inflammation on risk for adverse cardiovascular events after percutaneous coronary intervention: Results from a large single‐center registry. Issue 3 (22nd February 2020) - Aoi, Shunsuke; Baber, Usman; Kovacic, Jason C.; Mehran, Roxana; Aquino, Melissa; Dangas, George; Sweeny, Joseph; Vijay, Pooja; Shah, Srushti; Barman, Nitin; Moreno, Pedro; Kini, Annapoorna S.; et al.
Abstract: Purpose: Our study investigated the impact of coronary artery calcification (CAC) and systemic inflammation on risks for major adverse cardiovascular events (MACE) following percutaneous coronary intervention (PCI). Background: CAC and systemic inflammation are known to be associated with an increased risk of cardiovascular events. Methods: A total of 17, 711 consecutive patients who underwent PCI in our hospital between January 1, 2009 and December 31, 2015 were categorized according to the degree of CAC (moderate/severe vs. none/mild) and high‐sensitivity C‐reactive protein (hsCRP) level (≥2 vs. <2 mg/L). MACE was defined as death, myocardial infarction (MI), or target vessel revascularization (TVR) occurring over 1 year. Results: Within the four groups, patients with both moderate/severe CAC and elevated hsCRP ( n = 1, 814 [10.2%]) were older with more comorbid risk factors compared to those with moderate/severe CAC alone ( n = 1, 687 [9.5%]), elevated hsCRP alone ( n = 7, 597 [42.9%]) or neither abnormality ( n = 6, 613 [37.3%]). The analogous 1‐year MACE rates were 21.2, 14.9, 11.5, and 7.8%, respectively ( p ‐trend < .001). Results were unchanged after multivariable adjustment, suggesting synergistic adverse effects in patients with both CAC and elevated hsCRP. Conclusions: The presence of both moderate/severe CAC and systemic inflammation confers a synergistic effect on risk for MACE following PCI, indicating the need for novel or more intense therapeutic interventions to mitigate risk in such patients.